Congenital haemolytic anaemia resulting from glucose phosphate isomerase deficiency: genetics, clinical picture, and prenatal diagnosis. Issue 3 (June 1979) - Whitelaw, A G; Rogers, P A; Hopkinson, D A; Gordon, H; Emerson, P M; Darley, J H; Reid, C; Crawfurd, M A
Abstract : Glucose phosphate isomerase (GPI) deficiency with severe haemolysis and hydrops fetalis was found in the first child of unrelated, healthy Caucasian parents. The child died at 3 hours. Both parents were found to have 50% of normal red cell GPI activity and qualitative tests on their red cells and white cells showed that each was heterozygous for a different GPI variant allele associated with enzyme deficiency. Tests on the placenta showed that the propositus was a 'compound' heterozygote. Examination of amniotic cells obtained by amniocentesis on the mother at 28 weeks in her second pregnancy led to the prenatal diagnosis of GPI deficiency. This second child, a 'compound' heterozygote at the GPI locus indistinguishable from the first, was successfully treated by immediate exchange transfusion and subsequent blood transfusions.